A Study on the Effect of Housing on Growth Performance of Nellore Lambs - KASALA, VISHNU TEJA; Sreedhar, S; Chakravarthy, Kalyana (Indian Journal of Animal Production and Management, 2024)
A study was carried out to find out the effect of housing on growth performance of Nellore Jodipi lambs under tropical environmental conditions. Thirty weaned Nellore ram lambs of 3-4 months age were selected based on body weight (average initial body weight) and randomly divided into three groups of ten animals each. The lambs in Group-I were housed with morum flooring and asbestos roofing with tree shade, while Group-II lambs were housed with morum flooring and asbestos roofing without tree shade and Group-III lambs were housed with elevated slatted flooring and galvalume roofing without tree shade. Temperature and humidity values were significantly (P<0.05) different among all the groups. Lower mean maximum temperature (°C) values were observed in group III (35.53±0.28) when compared to group I (36.22±0.27) and II (37.29±0.25) and the lower average maximum relative humidity (%) was 69.59±2.92 in group III followed by group II (69.88±2.94) and I (70.65±2.96). The average body weight of lambs after 120 days in group I, II and III was 19.92±0.52, 18.89±0.32 and 22.26±0.44 kg, respectively. The mean ADG of Nellore lambs at different weekly intervals was 31.0±1.00, 23.0±1.00 and 49.0±1.00 g in group I, II and III, respectively. Significant (P<0.05) differences were observed in body weights and ADG among the three groups. It was concluded that the housing system of elevated slatted flooring with galvalume roofing proved to be effective in controlling heat stress and maintaining normal physiological responses for better growth performance of Nellore ram lambs.